Intensive land-use is associated with development status in port cities of Southeast Asia. (1st April 2023) - Dong, Yuqi; Zhou, Yu; Zhang, Li; Gu, Yu; Sutrisno, Dewayany
Abstract: Port cities in Southeast Asia (SEA) have been undergoing intensive land use and land cover change (LUCC) because of rapid socio-economic development in recent decades. However, various development statuses among these cities could result in divergent LUCC transitions and therefore affect the local ecosystem at different levels. This study investigated the historic land-use transition in the SEA port cities by classifying Landsat images from 1990 to 2020 with the random forest algorithm, and further integrated these patterns with land-use modeling to inform the future land uses under the current developing mode. DIVISON was used to assess land-use fragmentation and investigated its relationship with development levels represented by the average nighttime light index (ANLI). The results showed an intensive LUCC in SEA port cities in 1990–2020, with artificial surface increasing by 9.2% (175.9 km 2 ) of the total area, mainly converted from cultivated land which decreased by 136.9 km 2 . An inverted V-shaped relationship between fragmentation and development level was found at the landscape level and for cultivated land, in which both turning points (TPs) occurred in the mid-developed stage (ANLI = 41.1 and 20.0, respectively). Artificial surfaces tended to be more aggregated in later developed stages, showing a TP of ANLI around 53.2. Under the current developing mode, the aggregation trend will be generally continued for the next three decades, mainly resulting from the increased connection in artificial surfaces. The findings also highlighted a tradeoff between city development and agricultural production in SEA port cities, leading to increased food insecurity in more developed stages. Recent developments also negatively affected aqua ecosystems, such as aquaculture, mangroves, and natural waterbodies in several cities. This study underscored the importance of the sustainable LUCC strategy in SEA port cities and provides insights into rationalizing land-use policies for other port cities worldwide.